Good call [reflections on faith, family, and fowl] - Robertson, Jase, 1969- (HOWARD BOOKS, 2014)
The straight-faced, funny man of Duck Dyanasty has a real story to tell. Not a repeat of the previous Duck Dynasty books, Jase Robertson opens up about his personal family life, his childhood days with a drunken father, and how he came to faith.